Unravelling young COPD and pre-COPD in the general population - Borja G. Cosío; Ciro Casanova; Juan José Soler-Cataluña; Joan B. Soriano; Francisco García-Río; Pilar de Lucas; Inmaculada Alfageme; José Miguel Rodríguez González-Moro; Guadalupe Sánchez; Julio Ancochea; Marc Miravitlles (ERJ Open Research, 2023)
Background Chronic obstructive pulmonary disease (COPD) is commonly diagnosed when the airflow limitation is well established and symptomatic. We aimed to identify individuals at risk of developing COPD according to the concept of pre-COPD and compare their clinical characteristics with 1) those who have developed the disease at a young age, and 2) the overall population with and without COPD. Methods The EPISCAN II study is a cross-sectional, population-based study that aims to investigate the prevalence of COPD in Spain in subjects ≥40 years of age. Pre-COPD was defined as the presence of emphysema >5% and/or bronchial thickening by computed chromatography (CT) scan and/or diffusing capacity of the lung for carbon monoxide (DLCO) <80% of predicted in subjects with respiratory symptoms and post-bronchodilator forced expiratory volume in 1 s/forced vital capacity (FEV1/FVC) >0.70. Young COPD was defined as FEV1/FVC <0.70 in a subject ≤50 years of age. Demographic and clinical characteristics were compared among pre-COPD, young COPD and the overall population with and without COPD. Results Among the 1077 individuals with FEV1/FVC <0.70, 65 (6.0%) were ≤50 years of age. Among the 8015 individuals with FEV1/FVC >0.70, 350 underwent both DLCO testing and chest CT scanning. Of those, 78 (22.3%) subjects fulfilled the definition of pre-COPD. Subjects with pre-COPD were older, predominantly women, less frequently active or ex-smokers, with less frequent previous diagnosis of asthma but with higher symptomatic burden than those with young COPD. Conclusions 22.3% of the studied population was at risk of developing COPD, with similar symptomatic and structural changes to those with well-established disease without airflow obstruction. This COPD at-risk population is different from those that develop COPD at a young age.